Developing a human-centric de-icing system to increase airport capacity and operational safety - Yaghi, Ahmed; Blundell, James; Li, Wen-Chin (Chartered Institute of Ergonomics and Human Factors, 2024)
This research paper presents an innovative automated de-icing system designed to enhance operational efficiency, safety, and environmental sustainability at airports during cold weather conditions. Traditional manual de-icing methods, which are labour intensive and pose significant safety risks and environmental concerns, are inefficient and costly. The proposed system incorporates human-centric design principles and advanced automation technologies, including predictive modelling and real-time data analytics, to facilitate safer and more efficient de-icing operations with reduced physical labour and improved aircraft turnaround times. Drawing upon interviews with Bucharest International Airport subject matter experts, the research identified key operational, safety, and environmental challenges in current de-icing processes in order to provide relevant human-centric design requirements. Subsequent system development focused on minimizing human error and physical strain, streamlining equipment preparation, and reducing environmental impact through sustainable practices. The research underscores the need for further empirical testing to validate the system's effectiveness in real-world settings, offering a significant step forward in achieving safer, more efficient, and environmentally responsible airport de-icing operations.
https://ergonomics.org.uk/events-calendar/ehf2024.html
Keywords: airport capacity; de-icing system; human-centric design; operational safety; risk management